DAMPAK REKLAMASI DI KAWASAN PESISIR PULAU BATAM TERHADAP KEBERLANGSUNGAN HIDUP NELAYAN SEKITAR - Putra, Eric Elmayudi; Epriadi, Dedi (SCIENTIA JOURNAL, 2021)
BWS Sumatera IV Batam City in carryin out reclamation activities on the island of Putri Nongsa,Batam city evaluates the policies issued.The activities carried out on Putri Island actually have an impact on the economic development of the people arround Putri Island,especially fishermen.Therefore,it is necessary to evaluate policies so that the regulations implemented in the field run according to what was planned at the beginning.According to law No 1 of 2014 concerning the management of coastal areas and small islands,reclamation of coastal areas and small islands is carried out in order to increase the benefits and or added value of coastal areas and small islands in terms of technical,environmental and socio-economic aspects.The purpose of this study is to evaluate the impact felt by fishermen and also the surrounding community as one of the consequences arising from coastal reclamation activities in the island area of the city of Batam.Data Collection techniques are interviews,observation,and documentation.The research objects are employees of BWS Sumatera IV Batam City,fishermen,and the surrounding community.The research result is to evaluate reclamation activities that have an impact on the surrounding community carried out by BWS Sumatera IV Batam City which as a whole has not reached the standard because there are still gaps between related parties and society.Based on policy evaluation indicators,namely effectiveness,efficiency,sufficiency,equality,responsiveness,and efficiency,policy evaluation is still not effective and efficient enough so that this reclamation activity is still experiencing obstacles and obstacles in its implementation in the field which has not been able to have a significant impact on the economic sustainability of the community the surroundings.